2011
DOI: 10.4049/jimmunol.1002376
|View full text |Cite
|
Sign up to set email alerts
|

TCR Mimic Monoclonal Antibodies Induce Apoptosis of Tumor Cells via Immune Effector-Independent Mechanisms

Abstract: mAbs that recognize peptides presented on the cell surface by MHC class I molecules are potential therapeutic agents for cancer therapy. We have previously demonstrated that these Abs, which we termed TCR mimic mAbs (TCRm), reduce tumor growth in models of breast carcinoma. However, mechanisms of TCRm-mediated tumor growth reduction remain largely unknown. In this study, we report that these Abs, in contrast to several mAbs used currently in the clinic, destroy tumor cells independently of immune effector mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(42 citation statements)
references
References 41 publications
1
41
0
Order By: Relevance
“…When the more aggressive BT-20-A2 tumor was tested in this same model, RL21A administration yielded a .2-fold tumor reduction. This magnitude of tumor reduction is consistent with the previously reported in vivo anti-tumor activity of a TCRm directed toward a p68 peptide/HLA-A2 complex (35,43). The promising in vivo tumor reduction achieved through the targeting of HLA/peptide complexes with TCRm demonstrates that the HLA of cancerous tissues may offer a rich horizon of new complexes that can be successfully targeted by TCRm mAb.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…When the more aggressive BT-20-A2 tumor was tested in this same model, RL21A administration yielded a .2-fold tumor reduction. This magnitude of tumor reduction is consistent with the previously reported in vivo anti-tumor activity of a TCRm directed toward a p68 peptide/HLA-A2 complex (35,43). The promising in vivo tumor reduction achieved through the targeting of HLA/peptide complexes with TCRm demonstrates that the HLA of cancerous tissues may offer a rich horizon of new complexes that can be successfully targeted by TCRm mAb.…”
Section: Discussionsupporting
confidence: 77%
“…We have recently demonstrated that TCRm directly activates caspases, apoptosis, and cell death by signaling through specific MHC/peptide complexes (35), and we suspect that RL21A induced in vivo killing of BT-20-A2 tumors by the same mechanism. Indeed, Verma et al (35) showed immune effector-independent anti-tumor mechanisms in vivo using F(ab9) 2 fragments of a different TCRm in the same BT-20-A2 tumor model. Those findings and the modest ADCC and CDC activity observed in vitro for RL21A against BT-20-A2 tumor cells in the current study may point to a CDC-and ADCC-independent mechanism of action for RL21A in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As immunotoxin conjugates, these constructs have shown activity against breast and prostate cancer, and melanoma xenografts in mice. Mouse IgG2a mAbs specific for human chorionic gonadotropin (h-CG)-b, p68 RNA helicase and Her2 peptides presented by HLA-A0201 are also active in vivo [10]. Several mechanisms of action were observed in vitro, including ADCC, and surprisingly, CMC (which normally requires high antigen density) and direct induction of apoptosis through the JNK signaling pathway.…”
Section: Tcr-like/tcr-mimic Antibodiesmentioning
confidence: 99%
“…However, the immune system exerts pressure which often promotes selection for viruses or tumor capable of evading an effective CTL response. T-cell receptor mimicking (TCRm) monoclonal antibodies (mAbs) which recognize specific peptide/HLA-A*02:01 complexes such as those derived from breast cancer associated proteins, macrophage migration inhibitory factor (MIF [19][20][21][22][23][24][25][26][27] ) 3 and NY-ESO-1 157-165 , enable detection and destruction of breast cancer cells in the absence of an effective anti-tumor CTL response 4,5 . This representative work is focused on the HLA-A*0201 molecule, which is expressed by up to 30% of the population.…”
Section: Introductionmentioning
confidence: 99%